2016
DOI: 10.3892/ijo.2016.3620
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pigment epithelium-derived factor for neoadjuvant radiation therapy in patients with locally advanced rectal carcinoma

Abstract: The aim of the study was to investigate the prognostic value of pigment epithelium-derived factor (PEDF) in locally advanced rectal carcinoma (LARC) treated with neoadjuvant radiation therapy (nRT). The level of PEDF expressing was examined in LARC tissues treated with nRT by immunohistochemistry and the prognostic significance of PEDF was analysed by univariate and multivariate survival analyses. We forced expression of PEDF in highly metastatic LoVo cells. The clonogenic survival assay was used to test the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Histone lysine methylation and DNA methylation are highly interrelated, and these two systems rely on each other mechanistically for normal chromatin function (43,44). One previous study showed that PEDF promoter methylation status negatively correlated with the PEDF mRNA expression level in locally advanced rectal carcinoma tissues (45). Therefore, SMYD4 may influence PEDF expression via its potential effect on epigenetic modification.…”
Section: Discussionmentioning
confidence: 94%
“…Histone lysine methylation and DNA methylation are highly interrelated, and these two systems rely on each other mechanistically for normal chromatin function (43,44). One previous study showed that PEDF promoter methylation status negatively correlated with the PEDF mRNA expression level in locally advanced rectal carcinoma tissues (45). Therefore, SMYD4 may influence PEDF expression via its potential effect on epigenetic modification.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, Hou et al [ 37 ], Yi et al . [ 38 ], and Jiang et al [ 39 ] grouped tumors with grade G1-2 to be “low grade” and tumors with grade G3-4 to be “high grade”. Zhou et al [ 40 ] and Uehara et al [ 41 ] defined G1 tumors as “low grade” and G2-3 tumors as “high grade”; while Jang et al [ 39 ] did not provide grading information for the “low grade” and “high grade” groups in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Other than TNM stating, we are also interested in the association of PEDF protein expression with tumor histological grades. While reviewing the original studies, we noticed that tumors had been categorized into "low-grade" and Zhang [42] Li [43] Hou [37] Yi [38] Uehara [41] Jang [55] Lv [56] Jiang [39] Publication year "high-grade" groups based on the conventional cut-off criteria of each type of cancer (Table 1). Specifically, Hou et al [37], Yi et al [38], and Jiang et al [39] grouped tumors with grade G1-2 to be "low grade" and tumors with grade G3-4 to be "high grade".…”
Section: Association Of Pedf Protein Expression and Histological Grade Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Serum APOA1 level showed strong negative correlation with CRP and interleukin IL-8 levels and blood neutrophil count [ 43 ]. Our previous work showed that patients with high PEDF expression after nRT had better DFS in rectal cancer [ 44 ]. This study further implicated that PEDF might be a prognostic marker.…”
Section: Discussionmentioning
confidence: 99%